Analisis Kualitatif Kendala Dan Potensi Penerapan Internet of Things Pada Budidaya Ikan Air Tawar Di Perairan Kolong Bekas Tambang Timah - Dewi Tumatul Ainin; Nur Khasanah; Laily Muharani; Abang Naufal Faiz Fathurrahman (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2026)
This study provides an in-depth analysis of the constraints and potential for implementing Internet of Things (IoT) technology in freshwater fish aquaculture within former tin mining ponds in Bangka Regency. Former mining ponds represent non-conventional waters with significant potential for aquaculture, yet they face challenges related to extreme water quality conditions and infrastructure limitations. This research employed a qualitative approach with an intrinsic case study design. Data were collected through semi-structured interviews with 14 participants, comprising 10 fish farmers, 2 fisheries extension officers from the Marine and Fisheries Service, and 2 IoT technology experts, supplemented by participant observation at 3 pond locations and regional policy document analysis. Data analysis was conducted using thematic analysis following the Miles, Huberman, and Saldaña model, with source and method triangulation to ensure data trustworthiness. The findings reveal that despite substantial potential for IoT implementation—including real-time remote monitoring, early detection of water quality changes, operational efficiency improvements, and historical databases for trend analysis—implementation remains hindered by five critical constraints: (1) unstable or unavailable internet connectivity (reported by 78.6% of participants), (2) high initial investment costs (complained by 64.3% of participants), (3) low farmer capacity in operating digital technologies (only 57% possess adequate digital literacy), (4) environmental conditions prone to theft risks (reported by 43% of participants), and (5) conventional culture and habits that are difficult to change (reported by 36% of participants). Farmers' perceptions of IoT varied: 60% positive (optimistic about benefits), 25% neutral (interested but hesitant), and 15% negative (distrustful or fearful of technology). Based on these findings, this study recommends an IoT system design with an "offline-first" architecture that integrates local storage (32GB MicroSD) for data retention during network outages, alternative connectivity via LoRa (5–15 km range) and SMS gateway (minimal 2G signal) for areas without 4G coverage. Additionally, IoT-as-a-Service or technology cooperative business models are recommended to reduce initial investment barriers for small-scale farmers. This research makes a significant contribution to sustainable aquaculture literature by introducing the context of non-conventional waters (former tin mining ponds) with unique characteristics distinct from conventional ponds or tanks, particularly environmental conditions that affect IoT sensor durability. The finding that infrastructure and environmental contexts serve as important moderating variables in technology adoption enriches the Technology Acceptance Model (TAM), which has previously insufficiently explored contextual factors in marginal regions. Practically, this study provides an empirical foundation for developing context-specific technology accompaniment policies and strategies for former mining lands in Bangka Belitung, while opening opportunities for interdisciplinary research integrating aquaculture, IoT technology, and sustainable development in post-mining regions.